Youth-to-youth empowerment study to support health equity for urban American Indian/Alaska Native and Black adolescents in Denver Metro, Colorado, USA: a mixed methods, youth-centred aetiological study protocol - Dustin T Duncan; Roland S Moore; Brisa Sanchez; Nicole Tuitt; Arionna Hall; Yazira Martinez Dominguez; Anniah Hill; Oluwafikemi Samuels; Alexander Weiden; Nancy Rumbaugh Whitesell; Carol Kaufman (BMJ Public Health)
Introduction Promoting positive substance use and sexual health outcomes for urban American Indian and Alaska Native (AIAN) and Black youth requires multilevel approaches that address the underlying structural conditions that promote behavioural health inequities. However, researchers rarely employ this complex approach. Developing and operationalising a strengths-based conceptual framework grounded in the socioecological model is a critical first step to inform multilevel interventions to reduce these inequities.Methods and analysis Guided by the socioecological model, a youth-centred mixed methods approach will be employed to develop and evaluate a comprehensive multilevel conceptual framework of risks and protective factors associated with substance misuse and adverse sexual health behaviours among AIAN and Black youth of Denver Metro, Colorado. We will use multilevel structural equation modelling, with secondary and geographical data. The secondary data include the Healthy Kids Colorado Survey data (n=631 AIAN, n=5350 Black and n=30 557 non-Hispanic white), the Colorado Department of Education School View data (n=33 schools) and the American Community Survey data (n=73 neighbourhoods). We will also engage approximately 30 youth through scenario-based interviewing to capture perspectives on the constructs that are not captured in the secondary data. The quantitative and qualitative data will be integrated to elucidate a conceptual framework that will be used to develop and optimise a multilevel intervention to reduce adverse substance use and sexual health outcomes in AIAN and Black youth in Denver Metro, Colorado.Ethics and dissemination The results of the study will be shared at conferences, meetings and in published articles. Study findings will also be presented to the local community through presentations, social media, newsletters, flyers and brochures. The names of all participants, schools and neighbourhoods will be kept private. This study was approved by the Colorado Multiple Institutional Research Board (protocol number 21-4038).